2019
DOI: 10.17219/acem/104525
|View full text |Cite
|
Sign up to set email alerts
|

Could the super-pulsed CO2 laser be used for oral excisional biopsies?

Abstract: Background. The main purpose of a biopsy is microscopic examination and diagnosis. Keeping the margins of specimens safe and readable is always fundamental to detecting marginal infiltrations or malignant transformation. Numerous options and tools have been introduced for biopsy procedures. Lasers are one of these options that provide many enhancements to clinical and surgical biopsy procedures in comparison to scalpels.Objectives. The aim of the present study is to quantify the thermal artefacts in histologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Compared to the CO 2 laser, the blue diode laser showed both lower epithelial and connective tissue average thermal effects [38].…”
Section: Discussionmentioning
confidence: 96%
“…Compared to the CO 2 laser, the blue diode laser showed both lower epithelial and connective tissue average thermal effects [38].…”
Section: Discussionmentioning
confidence: 96%
“…The device tested here also appears to be safer than a 10,600 nm superpulsed CO 2 laser, when evaluated "in vivo", at 4.2 W in pulsed wave (PW) [8]. The higher tissue alteration caused by the CO 2 laser is a result of the greater power needed to achieve beam cutting action, especially for vascularized tissues, as the wavelength of the CO 2 laser has water as a target.…”
Section: Discussionmentioning
confidence: 88%
“…53 Tenore et al found the thermal effect of the CO2 laser was visible in all specimens and stronger in attached gingiva than in other anatomical locations. 30 Another study found that when the excision of essentially normal marginal mucosa encircling the tumor is reduced, the recurrence of Oral Squamous Papillomas is markedly increased. 31 In a study, CO2 and Er,Cr:YSSG lasers improved the quality of scars after 4 weeks, had superior cosmetic results, and did not need a second treatment session compared to diode and Nd:YAG laser groups.…”
Section: Results Of Individual Studies Oral Potentially Malignant Dis...mentioning
confidence: 99%